2012
DOI: 10.1039/c2ob06681e
|View full text |Cite
|
Sign up to set email alerts
|

Chemical generation of o-quinone monoimines for the rapid construction of 1,4-benzoxazine derivatives

Abstract: Highly reactive o-benzoquinone monoimines were chemically generated and successfully trapped with electron-rich olefins that led to the synthesis of hitherto unknown 1,4-benzoxazine derivatives. This unprecedented transformation was achieved by the oxidation of o-aminophenols bearing appropriate functionality on the arene residue with less expensive hypervalent iodine reagent in the presence of vinylic ethers or thioethers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…However, on switching to CoP2 , the desired transformation could be achieved and product 6 was obtained in 80% yield. Non-catalytic trapping of o -quinone monoimines has been reported earlier, but the method uses stoichiometric amounts of halogen containing oxidants, which is avoided in the reaction depicted in Scheme 5 [37].…”
Section: Resultsmentioning
confidence: 99%
“…However, on switching to CoP2 , the desired transformation could be achieved and product 6 was obtained in 80% yield. Non-catalytic trapping of o -quinone monoimines has been reported earlier, but the method uses stoichiometric amounts of halogen containing oxidants, which is avoided in the reaction depicted in Scheme 5 [37].…”
Section: Resultsmentioning
confidence: 99%
“…Among these chemical conversions, the oxidative substitution and/or addition occurring at the nitrogen center (route a, Scheme ) using metallic and non‐metallic oxidants typically constitutes the main reaction patterns, providing a variety of synthetically useful nitrogen‐containing building blocks and precursors (e.g., hydroxylamines, nitrosoarenes, nitroarenes, nitrones, amine oxides, diazonium salts, azides, hydrazines, azoarenes, and azoxyarenes) 1,3,4. Except for the above transformations with retention of the aromaticity of the parent ring A (route a), the reactions involving the oxidative dearomatization of arylamines (route b) are also documented for the synthesis of quinoids (e.g., quinol‐imines and derivatives,5 quinone‐imine ketals,6 quinone‐imines,7dj and quinone‐diimines7ac,e). Compared with the vast majority of literature reports on the classical oxidation of the arylamino moiety (route a),1,3,4 however, less attention has been paid to the development of methodologies based on the selective oxidative dearomatization of arylamines, especially those involving a new carbon‐carbon bond‐forming sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Bodipati et al [96] showed that the highly reactive o-quinone monoamine intermediates 139, generated by treatment of o-aminophenols 136 with PIDA, readily undergo completely regioselective [4 + 2] cycloadditions with vinyl ethers and phenyl vinyl sulfide to afford N-unsubstituted-1,4-benzoxazine derivatives 138 (Scheme 34).…”
Section: Intermolecular C-n/c-o Bond Annulationmentioning
confidence: 98%